Kant’s Teleology and the Problems of Bioethics - Martynova, Svetlana (Con-Textos Kantianos. International Journal of Philosophy, 2020)
One of the issues with which bioethics is concerned is defining the limits of the organism’s transformations by technology in order for humanity to avoid evil. Kant’s teleological power of judgment enables us to identify an organism and it allows nature to be transformed only insofar as it affirms a moral subject acting on the basis of autonomy as reason. I propose a new way of utilizing Kantian philosophy in bioethical knowledge. I ask: can we make judgments about nature via the principle of purposiveness? In answering this question, I clarify the following points. The first is Kant’s research into the foundations and reasons for using the teleological power of judgment. The second is the role of digital technology and how it complicates the use of the teleological power of judgment within the framework of bioethical knowledge. And the third is the preservation of the foundations for using the teleological power of judgment.